Estimation of net benefit from the proposed ban la hydropower project in nghe an province, Vietnam - Nguyen, Thi Hoang Hoa (Faculty of Social Sciences, 2005)
The construction and operatio of Ban La hydropower project will lead to a variety of changesin the local and wider enviroment. Many of the impacts will be beneficial, both at the regional and national level. Project implementation will have some socioeconomic impacts on communities in two districts upstream and nine districts downstream from the dam. Completion of Ban La project will supply water to two irrigation systems: North Nghe An Irrigation System and South Nghe An, which corner some 62,220 ha of irrigated area in Nghe An province. The construction of the project will also reduce flood peak in the downstream area and hence reducing flooddamages for riverine residents in the downstream area.